Pengaruh Budaya Organisasi dan Komitmen Organisasi terhadap Organizational Citizenship Behavior dengan Tipe Kepribadian sebagai Variabel Moderating pada Pusat Penelitian Kelapa Sawit PPKS/Rispa Medan - Deni Setiawan (Universitas Harapan Medan, 2020)
The purpose of this study is to determine the effect of organizational culture and organizational commitment on Organizational Citizenship Behavior and to determine the effect of personality types strengthening or weakening organizational cultural relations and organizational commitment to Organizational Citizenship Behavior. This type of research is associative research. The population in this study is the number of employees of the Medan PPKS / RISPA Palm Oil Research Center, amounting to 740 people and the sample used in this study was 88 people using the Slovin method. Data analysis techniques in this study are regression and MRA. The results showed that organizational culture had a positive and significant effect on organizational citizenship behavior, organizational commitment had no effect on organizational citizenship behavior, personality types strengthened the relationship between organizational commitment to organizational citizenship behavior, and personality types strengthened the relationship between organizational culture and organizational citizenship behavior.